People’s Republic of China: tax policy and employment creation - Klemm, Alexander; Coelho, Isaias; Duncan, Alan; Liu, Li (International Monetary Fund (IMF), 2018)
This report discusses the impact of tax policy, including social security contributions, on employment in China, covering both taxation of employed labor and small and medium-sized enterprises. The findings draw on economic theory, international experiences, as well as discussions with Chinese authorities during a workshop in Yangzhou and meetings in Beijing.